Are individual transferable quotas an adequate solution to overfishing and overcapacity? Evidence from Danish fisheries. (January 2018) - Merayo, Eugenia; Nielsen, Rasmus; Hoff, Ayoe; Nielsen, Max
Abstract: Individual Transferable Quotas stand in large parts of the fisheries economic literature as the panacea that solves all problems of overfishing and overcapacity of world´s fisheries. However, they are also criticized by a number of authors based on their negative social effects. Individual Transferable Quotas have been increasingly used during the past decades and are the main management system in a number of countries today. This paper provides evidence of the economic, social and environmental effects of one such system ten years after its introduction in Danish fisheries starting in 2003 with herring and being fully implemented from 2007. It is found that together with an important reduction in the fleet size, economic profitability improved. The direct contribution to GDP from the fleet in terms of economic return increased and indirectly through the capital and labour released from the fisheries sector, which have been absorbed by other sectors. Full-time employment has been reduced by 68% with fishermen salary largely unchanged, which might have affected the social cohesion in the local fishing communities negatively. However, no significant difference in the evolution of unemployment in local fishing communities compared to the national average was found. The Danish experience proves that Individual Transferable Quotas can be an adequate solution with regards to overfishing and overcapacity with also positive effects on the environment due to reduced fuel consumption and fishing activity. The social effects are ambiguous seeing that fisheries employment decreases; however, unemployment rates in the affected communities are below the national average. Highlights: Need to identify empirically the effects of ITQs, for policy considerations. The economic and environmental effect of ITQs may be generally positive. Social impact of ITQs is ambiguous and may depend on alternative job opportunities. Although ITQs might not rise unemployment, local effects cannot be dismissed. The impact of ITQs may depend also on exogenous factors, e.g. state of the stocks.